2013
DOI: 10.1007/s10142-013-0350-3
|View full text |Cite
|
Sign up to set email alerts
|

The GATA and SORLIP motifs in the 3-hydroxy-3-methylglutaryl-CoA reductase promoter of Picrorhiza kurrooa for the control of light-mediated expression

Abstract: Light upregulates the expression of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) in Picrorhiza kurrooa, an endangered medicinal herb. Upstream sequences of HMGR of P. kurrooa (PropkHMGR) were analyzed in relation to its role in light-mediated regulation of gene expression. GATA motif in PropkHMGR exhibited stronger DNA-protein interaction with the nuclear extract of dark-exposed plants in contrast to SORLIP that exhibited stronger binding with the nuclear extract of light-exposed plants. Analysis of PropkHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Light inhibits HMGR activity, while dark induces HMGR gene expression. The response of HMGR to light is low, and this process is mediated by light-responsive elements such as GATA and SORLIP motifs [52,64]. However, in this study, ultraviolet light up-regulated the expression of VvHMGR3, which means that light and ultraviolet light have different regulatory effects onHMGR activity.…”
Section: Hmgr Transcription Changes In Response To Various Environmental and Phytohormone Stimulicontrasting
confidence: 57%
“…Light inhibits HMGR activity, while dark induces HMGR gene expression. The response of HMGR to light is low, and this process is mediated by light-responsive elements such as GATA and SORLIP motifs [52,64]. However, in this study, ultraviolet light up-regulated the expression of VvHMGR3, which means that light and ultraviolet light have different regulatory effects onHMGR activity.…”
Section: Hmgr Transcription Changes In Response To Various Environmental and Phytohormone Stimulicontrasting
confidence: 57%
“…The presence of G-box and Box 4 elements in the PqHMGR promoter, possibly participating in the light response, has been confirmed. The light-responsive cis -elements have previously been found in promoters of HMGR genes from tomato, maidenhair tree ( Gingko biloba ), mulberry ( Morus alba ), kutki/kutaki ( Picrorhiza kurroa ), red sage ( Salvia miltiorrhiza ), and Andrographis paniculata [36,37,38,39,40,41]. The presence of a G-BOX element suggests that the isolated PqHMGR promoter may be homologous to PgHMGR1 .…”
Section: Discussionmentioning
confidence: 99%
“…The Genome Walking approach, thus, obtained a 1,034-bp 5 -upstream region of ShPLR (Figure 1 and Supplementary Figure 2), and a 785-bp region for ShSLD (Figure 2 and Supplementary Figure 2). Our previous experience in characterizing promoters of similar lengths in other plant species suggested that the present length of promoters was large enough to provide useful regulatory sequences controlling gene expression (Kawoosa et al, 2010(Kawoosa et al, , 2014Bhuria et al, 2016). The promoter sequences were submitted to NCBI with accession numbers such as OK574340 for ShPLR and OK574341 for ShSLD.…”
Section: Resultsmentioning
confidence: 99%